Engineering Liquid Hierarchical Materials with DNA‐Programmed Spherical Nucleic Acids - Zeyu Chen; Xu Chen; Dan Lu; Huating Kong; Jingyi Ye; Chunhai Fan; Honglu Zhang; Huan Zhang (Advanced Science)
Abstract Inspired by nature, the orchestration of self‐assembling building blocks into hierarchical superstructures offers a transformative approach to functional materials design. While significant advances have been made in engineering solid‐state hierarchical materials such as crystals and superlattices, creating dynamic, liquid‐like hierarchical materials remains a profound challenge. Herein, a universal and efficient method is introduced to construct spherical nucleic acids (SNAs) functionalized with diverse nucleic acids (NAs), including random DNA sequences, circular DNA (circ‐DNA), single guide RNA (sgRNA), messenger RNA (mRNA), and multi‐branched DNA independent of sequence, length, or topology. By examining spatial configuration and mechanical rigidity in DNA‐mediated bonding, precise hierarchical assembly of SNAs is enabled. Furthermore, using these multivalent SNAs as programmable molecule equivalents, liquid‐phase hierarchical materials via phase separation are successfully created, forming microscale SNA droplets. These metal condensates exhibit dynamic liquid‐like properties and stimuli‐responsiveness, including enhanced photothermal effects in living cells. Our findings provide fundamental insights into the formation and dynamics of liquid hierarchical materials, offering potentials for designing living‐matter‐inspired systems and advancing applications in biomedicine and responsive materials.